From Data to Design: An Investigation of Curriculum Development Needs - Aghnia Assifa Nadia; Ayu Muliahayati Nashir; Zaitun Qamariah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study highlights the importance of needs analysis in developing learner-centered curricula. Using a library research approach, it explores how investigative techniques—such as interviews, surveys, and classroom observations—can effectively uncover both explicit and implicit student needs. The analysis reveals that triangulating these techniques provides a more holistic and valid understanding of learners. Teachers are encouraged to take on the role of "curriculum detectives" who not only implement but also actively investigate and adapt the curriculum based on data and empathy toward student experiences. The study concludes that systematic and continuous needs analysis leads to dynamic, responsive, and inclusive curriculum design, fostering meaningful and transformation learning experiences.